Outorga onerosa do direito de construir e dinâmica do mercado imobiliário formal: planejamento e descaminhos na expansão urbana de Parnamirim RN (2008-2010) - Giesta, Josyanne Pinto (2013)
The `Outorga Onerosa do Direito de Construir - OODC` (Public Concession of Building Rights), instrument instituted by The City Statute in 2001, has as main objective the recovery of urban property, seeking for a fair distribution the urbanization benefits. The possibility of usage of the OODC instrument is linked to the maximum utilization coefficient, determined to specific areas in accordance to existing infrastructure conditions, further taking into account the formal real estate market, expansion axis and crowding. Being an instrument which establishes values to be paid for a better use of land, it maintains a narrow relation to the real estate, incentivizing or discouraging the crowding in specific areas. The present study investigates the relationship between the criteria for the making of the Public Concession of Building Rights instrument and the dynamics of the formal real estate market. It takes as empiric universe Parnamirim (RN), part of the Natal Metropolitan Area (RN), focusing on the application of the OODC in the period of 2008-2010. It seeks to better understand the necessary basis for the formulation of the instrument, about how it works and its relation to the formal real estate market. It aims to depict the formal real estate market by presenting the production of urban space in Parnamirim in terms of intensity and nature of the real estate, furthermore identifying the licensed properties through the application of the municipality instrument. For the conclusion, it is discussed the criteria for the formation of OODC, its relationship to the dynamics of the formal real estate market and its influencing possibilities in the processes of usage and occupation of land in the context of urban planning